2020
DOI: 10.2215/cjn.05190420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urate-Lowering Therapy on Cardiovascular and Kidney Outcomes

Abstract: Background and objectivesSeveral clinical practice guidelines noted the potential benefits of urate-lowering therapy on cardiovascular disease and CKD progression; however, the effect of this regimen remains uncertain. In this systematic review, we aimed to evaluate the efficacy of urate-lowering therapy on major adverse cardiovascular events, all-cause mortality, kidney failure events, BP, and GFR.Design, setting, participants, & measurementsWe systematically searched MEDLINE, Embase, and the Cochrane dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 40 publications
3
56
0
1
Order By: Relevance
“…In line with these concerns are the results of a very recent meta-analysis including 28 prospective, randomized, controlled trials assessing the effects of ULT for at least six months on CV or kidney outcomes [ 39 ]. Chen Qi et al found that ULT was associated with the reduction of blood pressure and retardation of the decline in GFR overtime.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these concerns are the results of a very recent meta-analysis including 28 prospective, randomized, controlled trials assessing the effects of ULT for at least six months on CV or kidney outcomes [ 39 ]. Chen Qi et al found that ULT was associated with the reduction of blood pressure and retardation of the decline in GFR overtime.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to obtain further information is meta-analysis of already available trials. A recent meta-analysis that includes both PERL and CKD-FIX as well as 26 additional trials concluded that urate-lowering therapy did not show benefits on major adverse cardiovascular events [risk ratio (RR) 0.93 (95% CI 0.74–1.18)] and all-cause mortality [RR 1.04 (95% CI 0.78–1.39)] or kidney failure [RR 0.97 (95% CI 0.61–1.54)], thus confirming the futility of urate lowering on hard endpoints [ 59 ]. It should be noted that the meta-analysis was not limited to CKD patients or to trials with a kidney function primary endpoint.…”
Section: Will There Be Any Additional Information Available In the Nementioning
confidence: 93%
“…Furthermore, no evidence for an acute effect of allopurinol on eGFR was observed in the first 16 weeks [mean between-group difference −0.89 mL/min/1.73 m 2 (95% CI −2.15–0.37)] of CKD-FIX [ 57 ]. Indeed, experience from other trials and a recent meta-analysis suggest that the difference in eGFR between the urate-lowering and control groups decreases rather than increases over time [ 45 , 59 ].…”
Section: Recent Developments Regarding Efficacy Of Nephroprotection Bmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 1,134,073 participants showed a positive dose-response association between uric acid levels and cardiovascular disease mortality risk [ 11 ]. Hyperuricemia is common in chronic kidney disease (CKD) patients [ 12 ], and several studies have also shown a relationship between serum urate levels and kidney damage [ 13 , 14 , 15 , 16 ]. Urate-lowering therapy statistically significantly improved estimated glomerular filtration rate (eGFR) and serum creatinine and serum creatinine [ 17 ], and reduced the incidence of kidney failure events [ 18 ].…”
Section: Introductionmentioning
confidence: 99%